Fenomena "No Viral No Justice" di Indonesia: Disrupsi Legitimasi Institusional dan Dilema Keadilan Selektif di Era Jaringan - Febrian Rizky Akbar; Dhikma Heradika (Journal of Innovative and Creativity, 2025)
The "no viral no justice" (NVNJ) phenomenon reflects a condition wherein the resolution of a legal or social case in Indonesia only gains attention or concrete action from authorities and competent institutions after the case becomes viral on social media. This research analyzes the dynamics of this phenomenon through the integration of legal sociology perspectives, digital communication, and critical justice theory. The research employs a qualitative approach with triangulation of literature review, digital discourse analysis of viral cases during the 2023-2024 period, and comparative examination. Research findings demonstrate that virality functions as an effective mechanism of mass amplified pressure in accelerating institutional response. However, dependence on virality potentially creates selective justice, threatens the principle of equal treatment (Rawlsian Justice), and erodes the rational-legal legitimacy (Weberian) of legal institutions. This phenomenon indicates the existence of a profound deficit in public trust toward formal bureaucratic channels. To address the dilemma of selective justice, transparent and proactive reporting system reforms are required, strengthened judicial ethics in facing public intervention, and enhanced digital legal literacy. This article contributes to legal sociology literature by introducing the Selective Justice Trilemma model as an analytical framework for NVNJ.